Portion Control: A Key to Weight Management - Cassie C. Gaisser; Karla P. Shelnutt (EDIS)
Americans are eating more calories than ever before. Along with this increase in calories, portion sizes have grown larger over the years. Understanding portion control can help you eat the right amount of food to maintain a healthy weight. Learn more in this 5-page fact sheet written by Cassie C. Gaisser and Karla P. Shelnutt and published by the UF Department of Family Youth and Community Sciences, April 2011.